The Impact of Increasing Price of Imported Soybean to Words The Income of Tofu Entrepreneurs of Jatiroto, Wonogiri District - Narimo, Sabar; Budiyanto, Sapta Mei; Wulandari, Intan Tri (Proceedings International Conference on Education Innovation and Social Science, 2022)
This study aims to explain how much local soybean production is, to explain how much soybeans are needed for tofu entrepreneurs in Mojopuro Village, Jatiroto District, Wonogiri Regency, and to explain how much the price increase is felt by tofu entrepreneurs in Mojopuro Village, Jatiroto District, Wonogiri Regency. The problem in this study is the increase in soybean prices which has an impact on the income of tofu entrepreneurs where their income has decreased since the increase in the staple of their tofu production, namely imported soybeans. The method used in this study is qualitative with a case study design. Meanwhile, data collection techniques use interview and documentation techniques. To test the validity of the data used in this study, namely triangulation techniques. In this study, the results of the study obtained that the large number of local soybean production is still insufficient for the needs of tofu entrepreneurs, especially in Mojopuro Village, Jajtiroto District, Wonogiri Regency, because local soybean production in that place is still relatively low. The need for soybeans is also different because the production process itself is also different every day according to market needs or market demand. The increase in soybean prices is indeed very worried by entrepreneurs knowing that if there continues to be an increase, inevitably they will continue to look for strategies so that production costs are covered, but the profits they get will be smaller if the increase in imported soybeans continues to occur in Indonesia.